(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
MQTT is a communication protocol for exchanging messages between clients via MQTT broker and is used to build many IoT systems. Currently, various tools have been developed to help measure the performance of application systems using MQTT. However, because they are all versatile tools, a dedicated test system that meets the purpose of the application system needs to be built on their behalf. But building a test system is not that simple. In this paper we discuss a case of building a test system for measuring U-Mosquitto’s performance, which has modified the open source Mosquitto broker to handle urgent messages with priority, and some issues to be considered in the process. In particular, they include selection of the server computer, the structure of the test program, the use of appropriate threads for the client, the appropriate number of clients, the appropriate workload per client, clock synchronization between clients, protocol analyzer issues, and other issues. Our experiences and considerations on these issues are expected to be a good guide for building a test system to measure the performance of MQTT application systems.